Pengaruh Pijat Oksitosin terhadap Kuantitas ASI pada Ibu Pasca Melahirkan di Rumah Sakit X - Hanny Desmiati; Boy S Sabarguna; Nuntarsih Nuntarsih; Mardi Yana; Restu Octasila; Siti Dariyani; Dorsinta Siallagan; Reni Nofita; Widya Tri Hastuti; Rochmawati Rochmawati (Pusat riset dan Inovasi Nasional, 2025)
Inadequate breast milk production remains a significant challenge in achieving exclusive breastfeeding success during the postpartum period. This study aimed to analyze the effectiveness of oxytocin massage intervention on breast milk quantity among postpartum mothers at Hospital X. A quasi-experimental design with one-group pretest-posttest approach was employed, involving 17 postpartum mothers who met the inclusion criteria. Data collection utilized demographic questionnaires and measuring instruments to assess milk volume before and after the intervention. Oxytocin massage was performed using back massage technique for 30-60 minutes duration. Statistical analysis employed Wilcoxon signed-rank test due to non-normal data distribution. Results demonstrated significant improvement in milk volume from mean 12.95 ml (pretest) to 50.59 ml (posttest) with p-value 0.000 (p<0.05), indicating statistical significance. The intervention showed substantial effectiveness with approximately 291% increase from baseline condition. These findings suggest that oxytocin massage represents an effective non-pharmacological modality for optimizing lactogenesis through neurohormonal stimulation mechanisms, supporting milk ejection reflex enhancement in postpartum mothers.